Current status of the cryopreservation of embryogenic material of woody species - Ballesteros, Daniel; Martínez, María Teresa; Sánchez-Romero, Carolina; Montalbán, Itziar Aurora; Sales, Ester; Moncaleán, Paloma; Arrillaga, Isabel; Corredoira, Elena (Frontiers in Plant Science, 2024)
Cryopreservation, or the storage at liquid nitrogen temperatures (-196ºC), of embryogenic cells or somatic embryos allows their long-term conservation without loss of their embryogenic capacity. During the last decade, protocols for cryopreservation of embryogenic material of woody species have been increasing in number and importance. However, despite the large experimental evidence proved in thousands of embryogenic lines, the application for the large-scale conservation of embryogenic material in cryobanks is still limited. Cryopreservation facilitates the management of embryogenic lines, reducing costs and time spent on their maintenance, thus limiting the risk of the appearance of somaclonal variation or contamination. Somatic embryogenesis in combination with cryopreservation is especially useful to preserve the juvenility of lines while the corresponding clones are being field-tested. Hence, when tree performance has been evaluated, selected varieties can be propagated from the cryostock. The traditional method of slow cooling or techniques based on vitrification are mostly applied procedures. For example, slow cooling methods are widely applied to conserve embryogenic lines of conifers. Desiccation based procedures, although simpler, have been applied in a smaller number of species. Genetic stability of the cryopreserved material is supported by multiloci PCR-derived markers in most of the assayed species, whereas DNA methylation status assays showed that cryopreservation might induce some changes that were also observed after prolonged subculture of the embryogenic lines. This article reviews the cryopreservation of embryogenic cultures in conifers, fruit species, deciduous forest species and palms, including a description of the different cryopreservation procedures and the analysis of their genetic stability after storage in liquid nitrogen.